Evaluation of wheat gluten and spray-dried animal plasma on growth performance of nursery pigs - Lawrence, K.R.; Hastad, C.W.; Hanni, S.M.; Barker, M.R.; James, B.W.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of 440 weanling pigs (initially 14.3 lb) were used in two studies to evaluate the effects of increasing wheat gluten (WG) and spray-dried animal plasma (SDAP) on growth performance of early weaned pigs. In Exp. 1, the six dietary treatments included a negative control, containing no wheat gluten or animal plasma, the control diet containing either 3, 6, 9, or 12% lightly modified spray-dried wheat gluten, and a positive control diet containing 5% spray-dried animal plasma. The diets containing 9% WG and 5% SDAP had the same amount of soybean meal to make a direct comparison of the two protein sources. From d 0 to 7, 7 to 14, and 0 to 14, increasing wheat gluten had no effect on ADG, ADFI, or feed efficiency. From d 0 to 7, pigs fed 5% SDAP had greater ADG than pigs fed the diet containing 9% WG but similar ADG to pigs fed the negative control. For the common period, d 14 to 28, a quadratic (P<0.01) response was observed for feed efficiency with F/G becoming poorer as wheat gluten was added up to 9% then improving as wheat gluten increased up to 12%. In Exp. 2, the five dietary treatments included a negative control, which contained no SDAP or WG, or the control diet with 4.5% and 9% WG, or 2.5% and 5% SDAP. The wheat gluten source used was different than in Exp. 1 and was enzymatically hydrolyzed. The diets containing 4.5% and 9% wheat gluten contained the same amount of soybean meal as the diets with 2.5% and 5% SDAP, respectively. From d 0 to 7 and 0 to 14, increasing SDAP increased (P<0.04) ADG. Increasing WG had no effect. There were no differences found in ADG from d 7 to 14 and no differences found in feed intake from d 0 to 7. No differences (P<0.05) were found in feed efficiency. During the common period, d 14 to 35, no differences were found in ADG and ADFI. Pigs previously fed the diets containing 2.5% and 5% SDAP had (P<0.05) the best feed efficiency with the pigs previously fed the control having the worst. The pigs fed the diets containing 4.5% WG and 9% WG were intermediate in efficiency. These results suggest that increasing WG in diets fed immediately after weaning produced no improvement in growth performance relative to SDAP.
Keywords: Wheat gluten; Spray-dried animal plasma; Swine